1997
DOI: 10.1136/thx.52.12.1081
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of passive smoking. 3. Parental smoking and prevalence of respiratory symptoms and asthma in school age children

Abstract: Abstractthe early 1970s, 1-3 since when many epidemiological studies have reported on the Background -A systematic quantitative review of the evidence relating parental association of parental smoking and respiratory diseases throughout childhood. The US smoking to the prevalence of asthma and respiratory symptoms was conducted Environmental Protection Agency Review 4 which was essentially narrative concluded that amongst school age children. Methods -Sixty relevant studies were the evidence causally relating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
213
1
14

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(254 citation statements)
references
References 91 publications
(10 reference statements)
16
213
1
14
Order By: Relevance
“…Cohort studies have also shown increased risk of developing adult asthma from ETS (88), including occupational exposures (89). Among 3,914 nonsmoking adults followed 10 years, the relative risk for asthma onset from 10 years of working with a smoker was 1.45 (95% CI 1.21, 1.75) (85). A large survey of 4,197 never-smoking adults showed an elevated risk of physician-diagnosed asthma from any ETS exposure [OR 1.39 (95% CI 1.04-1.86)] but no increased risk of allergic rhinitis (90).…”
Section: Epidemiologic Evidence For Pollutant Mixtures Containing Pahmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohort studies have also shown increased risk of developing adult asthma from ETS (88), including occupational exposures (89). Among 3,914 nonsmoking adults followed 10 years, the relative risk for asthma onset from 10 years of working with a smoker was 1.45 (95% CI 1.21, 1.75) (85). A large survey of 4,197 never-smoking adults showed an elevated risk of physician-diagnosed asthma from any ETS exposure [OR 1.39 (95% CI 1.04-1.86)] but no increased risk of allergic rhinitis (90).…”
Section: Epidemiologic Evidence For Pollutant Mixtures Containing Pahmentioning
confidence: 99%
“…A recent meta-analysis concluded that studies showed an excess incidence of wheezing in smoking households, particularly in nonatopic children, suggesting a "wheezy bronchitis" pattern; however, in children with diagnosed asthma, parental smoking was associated with greater severity rather than incidence (78). A quantitative meta-analysis of studies up to April 1997 for 25 studies of asthma prevalence showed a pooled odds ratio (OR) for asthma of 1.21 (95% confidence interval [CI], 1.10-1.34) if either parent smoked (85). Well-conducted panel studies are still needed to evaluate acute exposure-response relationships using repeated measures methods.…”
Section: Epidemiologic Evidence For Pollutant Mixtures Containing Pahmentioning
confidence: 99%
“…• persistent decreased lung function, [106][107][108][109]137,139,149,154 amplified in children with cystic fibrosis, 16 • infections, 137,139,151,[154][155][156][157] • bronchiolitis, 158 wheezing, 47 and use of bronchodilating drugs, 47…”
Section: Effects On the Child Of Shs Exposurementioning
confidence: 99%
“…A exposição pré e pós-natal à fumaça ambiental do tabaco (FAT) constitui um fator determinante na morbidade respiratória e na redução prematura da função pulmonar em crianças [18][19][20] . Demonstrou-se que a exposição à FAT, tanto in utero quanto pós-natal, influencia a frequência dos sintomas respiratórios 21,22 , havendo uma relação dose-dependente entre a dose de FAT (um ou dois pais fumantes), os sintomas respiratórios e os índices espirométricos 18,19,23 .…”
Section: Introductionunclassified
“…Demonstrou-se que a exposição à FAT, tanto in utero quanto pós-natal, influencia a frequência dos sintomas respiratórios 21,22 , havendo uma relação dose-dependente entre a dose de FAT (um ou dois pais fumantes), os sintomas respiratórios e os índices espirométricos 18,19,23 . No entanto, nenhum nível de exposição passiva à fumaça é seguro 24 .…”
Section: Introductionunclassified